Practice of Traditional Medicine and Associated Factors Among Residents in Eastern Ethiopia: A Community-Based Cross-Sectional Study - Nigussie, Shambel; Godana, Abduro; Birhanu, Abdi; Abdeta, Tilahun; Demeke, Fekade; Lami, Magarsa; Gemechu, Kabtamu; Eyeberu, Addis; Bogale, Kasahun; Dechasa, Deribe Bekele; Getachew, Tamirat; Negash, Abraham; et al. (Frontiers in Public Health, 2022)
Abstract Introduction: Although the Practice of traditional medicine is accorded great importance worldwide, it seems to face a notable challenge. A notable challenge is the lack of a reference standard for determining the appropriate utilization of traditional medicine for patients. There is little evidence about the usual utilized traditional medicine in the study area. Therefore, this study aimed to assess practice of traditional medicine and associated factors among residents in Eastern Ethiopia. Methods: A community-based cross-sectional study was conducted from January 20, 2022 to February 20, 2022. About 818 study participants were recruited using a systematic random sampling technique. Data were collected by face-to-face interviews. The collected data were analyzed using Statistical Package for Social Sciences (SPSS) version 22 computer software. The association between an outcome variable and independent variables was assessed using binary logistic regression and the strength of association was presented using Adjusted Odd Ratio (AOR)with its 95% confidence intervals (CI). Result: A total of 803 participants were included in the final analysis with a 98.2 % response rate. From the total study participants, 563 (70.1%) [95%CI:66.8-73.3] had used traditional medicine in the past six months. Factors such as being farmer [AOR = 1.06; 95%CI: (1.03-3.7)], having a diploma degree or higher [AOR=3.2, 95% CI (1.4-7.3)] and having no history of chronic disease [ AOR = 0.21; 95% CI: (0.1- 0.5)] were significantly associated traditional medicine practice. Conclusion: The proportion of traditional medicine practice was high. The most commonly utilized traditional medicines were Damakase, Tenadam, Zingibil and Erate. A national health policy should give a great emphasize on rational utilization of traditional medicine.